ASSESSING THE POSSIBILITIES FOR THE NATURAL SETTLEMENT OF WESTERN ROCK LOBSTER - Phillips, Bruce; Melville-Smith, R.; Thomson, A.; Rossbach, M. (2007)
Previous studies have shown that western rock lobster pueruli and post-pueruli shelter in small holes and crevices and that suitable shelter in the inshore environment is limited. It is considered that by providing suitable shelter, the survival of this life-stage could be substantially enhanced, leading to increased production in the wild capture fishery. This project was developed to design suitable shelters, which can be used to test this proposal.A series of laboratory experiments were conducted to investigate the number, size and positioning of holes that might be suitable for post-pueruli shelters in the marine environment. The study found that: The number of post-pueruli in an experiment changed the hole occupation distribution patterns; Post-pueruli preferred the under face of the block and preferred to occupy holes in the vertical faces rather than the top of the block; Post-pueruli preferred the outer holes on a block face, rather than the central holes; Post-pueruli preferred holes further away, rather than closer to, similar sized post-pueruli, but would occupy holes close together rather than no hole at all; Smaller post-pueruli preferred the outer holes of a block face rather than those nearer to larger post-pueruli in the centre of the face; and The presence of predators did not affect hole occupancy distribution patterns.From these results, we estimated the number and dimensions of settlement habitats needed for a scientific field test to demonstrate that it is possible to increase survival of the post-pueruli. An area of 0.3 ha was estimated as a suitable sized area for such a demonstration. Based on settlement data that has been collected in previous studies in Western Australia, it is estimated that up to 30,000-pueruli settle per hectare in very good seasons of settlement. This means that suitable settlement habitats should offer at least 30,000 holes per hectare if each hole were to accommodate a puerulus. However, settlement normally occurs over an extended period and therefore not all of the holes need to be of the smallest size (12 mm in diameter and 50 mm deep). This study has assumed that the allocation of holes per hectare of coastline needs to be 15, 000 of 12 mm diameter holes, 10,000 of 20 mm and 5,000 of 30 mm. The holes would be 50, 80 and 120 mm deep, respectively. The distribution of the 12 mm holes will be at least 30 mm from its nearest neighbouring hole, while the larger diameter holes will be 60 and 120 mm from their nearest neighbouring holes.The project team, in collaboration with Marine Engineers in the Centre for Marine Science and Technology at Curtin University of Technology, has proposed two types of device suitable for field-testing as puerulus survival enhancement devices. Both devices are concrete blocks with holes in the side only.The smaller of the two block designs would be approximately 0.25 m high and 0.4 m square, weighing 85 kg and containing 50 holes. 200 of such devices would be required for a 10,000 hole (0.3 hectare) trial. The larger device would be approximately 0.4 m high and 1 m square, weighing 1,000 kg and containing 240 holes. 42 of such devices would be required for a 0.3 hectare trial. Both devices are robust, capable of tolerating wave action in depths of less than 10 m, and will be capable of surviving deployment for periods of at least three years before recovery.A cost-benefit analysis was impossible to achieve; fixed costs such as the price of concrete for manufacturing the blocks are known, but too many other inputs (such as the manufacture costs of the blocks) to such an analysis are unknown.A research plan for a field test of the enhancement devices has been developed and will be discussed with industry.